Molecular design of ferrocene-based novel polymer using click chemistry via chemoselective polymerization and investigation of electrical properties as organic Schottky diode - Biryan, Fatih; Çelik, Hilal; Çalışkan, Eray; Koran, Kenan (Elsevier Ltd, 2023)
Organic Schottky diodes are electronic devices that consist of a metal–semiconductor junction formed with an organic polymer as the semiconductor material. This work synthesized cinnamic acid side chain bearing polymer and its ferrocene-modified polymer. Thermal stability, dielectric and electrical properties of the initial polymer and the modified one were examined and the addition of a ferrocene unit to the initial polymer clearly improved the optical and electrical properties of the target polymer. Due to the influence of ferrocene, the dielectric constant increased from 8.69 to 18.92. Additionally, it was discovered that the ac conductivity value raised from 6.40x10?9 to 2.64x10?8. The Al/modified-polymer/p-Si structure exhibits an ideality factor of 2.22, a barrier height of 0.61 eV, and a reverse bias current of 1.28 10?5 A in the dark, according to the I-V measurements. These results demonstrated the fabricated diodes have a rectifier behavior. This diode exhibits unique electrical properties due to the characteristics of the organic polymer. © 2023 Elsevier Ltd
Keywords: Click chemistry; Dielectric; Ferrocene based polymer; Schottky diode